Analisis Perkembangan Peserta Didik dalam Aspek Kognitif, Sosial, dan Emosional pada Proses Pembelajaran - Dwi Nomi Pura; Rohayu Fadilla; Rara Sartika; Nuriana Nuriana; Susanti Susanti (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Student development is a process of change encompassing cognitive, social, emotional, and physical aspects that occurs gradually according to age. Understanding this development is important for educators in adapting the learning process to student characteristics. This study aims to analyze student development based on a literature review. The method used is a literature study by examining various relevant scientific sources regarding student development. The results of the study indicate that student development includes cognitive development related to thinking skills, social development in interactions with the environment, and emotional development in controlling feelings. The conclusion of this study shows that understanding the stages of student development is very important as a basis for designing an effective learning process that is appropriate to student needs.